SENSITIVE POTENTIOMETRIC SENSOR TO IONS OF LEAD (II) - K. E. Magomedov; S. D. Tataeva; V. S. Goryachaya (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Sensitive potentiometric sensor to ions of lead (II) is made by optimizing the composition of the plasticized membrane. Electrochemical and analytical performance of the electrode are established. The slope of the electrode function is 26,7533 ± 1,09038 mV / dec. The linear range of operation is 0,1- 1 • 10-5 M. The ions of zinc, cadmium, mercury, and to a lesser extent copper can have theinterfering effect of the determination of lead ions. Ions of some alkali and alkaline earth metals.do not interfere with the definition.